Los alumnos con problemas de conducta. Claves para la formación del profesorado - Marta Sandoval Mena; Cecilia Simón Rueda (Universidad de La Rioja, 2013)
Educational responses to emotional and behavioural difficulties adolescents are challenge for many teachers. The lack of information may difficult the docent labour. In this article the role of the teacher is analysed through the direct intervention with the students. As well as the teacher instruction taking into account personal, professional and institutional factors closed related with the competence improvement in this area. The main aim is to provide clues about some essentials variables that must been considered in order to design teacher's instructions programmes.